Valores pessoais do estudante estrangeiro no Brasil: estudo com os alunos do PEC-G - Rodrigues, Veridiana Sefrin Novaes (2009)
There is today increased integration between markets, with a continuous flow of people, products and processes from one country to another for various reasons, among which is the search for better education and professional qualification. One such example is the group of students of the Programa Estudante-Convênio Graduação (PEC-G, Undergraduate Student- Exchange Program), a bilateral program through which the Brazilian government offers educational cooperation to developing countries in Africa, Asia, Latin America and the Caribbean. This program offers benefits to students, such as being excused from the entrance examination and not paying educational fees for the undergraduate course taken in Brazil. In the present study we investigated, initially in an exploratory manner and subsequently in a descriptive manner, the perception of values (based on the Schwartz Value Survey) of PEC-G students regarding the attributes of the Brazilian institutions of higher education (in accordance with the Means-End Chain) using the Laddering technique. Among the set of values that form the cognitive structure of the population investigated we highlight competence and social recognition. Among the attributes given to the institutions of higher education, we highlight quality of teaching and research, qualification of professors and infrastructure. The results of the present study can be used by the Brazilian institutions of higher education and the public organs involved with PEC-G in order to focus their marketing strategies on foreign students and on the countries participating in the program.